2021
DOI: 10.1038/s41598-021-03650-9
|View full text |Cite
|
Sign up to set email alerts
|

Air quality assessment and pollution forecasting using artificial neural networks in Metropolitan Lima-Peru

Abstract: The prediction of air pollution is of great importance in highly populated areas because it directly impacts both the management of the city’s economic activity and the health of its inhabitants. This work evaluates and predicts the Spatio-temporal behavior of air quality in Metropolitan Lima, Peru, using artificial neural networks. The conventional feedforward backpropagation known as Multilayer Perceptron (MLP) and the Recurrent Artificial Neural network known as Long Short-Term Memory networks (LSTM) were i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 56 publications
(60 reference statements)
0
24
1
Order By: Relevance
“…On the contrary, positive and direct correlations were calculated (r WS-PM 10 − anual(0.40526) ), especially for summer (r WS-PM 10 (0.55296) ) and autumn (r WS-PM 10 (0.56274) ). These values are higher than other studies reported in Lima 34 , indicating influence on PM 10 dispersion, resuspension and transport, including its decrease with the simultaneous diminution of wind 50 . The non-parametric regression produced a coefficient of determination R 2 = 0.182 , close to other studies on the same variable 13 (Fig.…”
Section: Air Quality Indexescontrasting
confidence: 73%
See 1 more Smart Citation
“…On the contrary, positive and direct correlations were calculated (r WS-PM 10 − anual(0.40526) ), especially for summer (r WS-PM 10 (0.55296) ) and autumn (r WS-PM 10 (0.56274) ). These values are higher than other studies reported in Lima 34 , indicating influence on PM 10 dispersion, resuspension and transport, including its decrease with the simultaneous diminution of wind 50 . The non-parametric regression produced a coefficient of determination R 2 = 0.182 , close to other studies on the same variable 13 (Fig.…”
Section: Air Quality Indexescontrasting
confidence: 73%
“…Similarly, the Weather Research and Forecasting-Chem (WRF-Chem) model was applied to develop an operational forecast system for air quality in the Metropolitan Area of Lima and Callao (MALC) 12 . Air quality for PM 10 was also evaluated in other districts of Lima through the application of artificial neural networks (ANN), observing certain difficulties for its prediction in stations with critical pollution episodes 34 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…For future research, we can apply other univariate models, such as Recurrent Neural Network (RNN), Long Short-Term Memory (LSTM) [40,41], and bootstrap-based models, and develop a hierarchical time-series forecast strategy to compare with the classical structure applied in this study. Finally, another avenue for future work would be to study the multivariate models (such as vector autoregressive, Bayesian vector autoregressive, artificial neural networks models with multiple features in the input layer) and compare with the univariate approach.…”
Section: Discussionmentioning
confidence: 99%
“…is paper believes that the socalled learning evaluation is under the guidance of the national education policy, under the guidance of the education policy, based on the implementation requirements of specific teaching objectives, applying the theories and methods of systematic science and responding to the realization of the teaching objectives in various teaching and learning processes. To establish an objective evaluation standard system, measure the relevant data and data collection, display, and inspection and make a relatively objective value judgment [7,8]. Learning evaluation is a systematic investigation of teaching effects or all aspects of student development according to certain standards and value analysis and judgment based on the acquisition of sufficient data.…”
Section: Learning Evaluationmentioning
confidence: 99%